Pengaruh Kebijakan Badan Usaha Milik Desa (BUMDES) dan Pengembangan Wisata Halal terhadap Meningkatkan Pendapatan Masyarakat (Studi Kasus Pemandian Aek Milas Dano Hutaraja) - Dewi Sundari Tanjung; Yurmaini Yurmaini; Khoirunnisa Lubis (HIBRUL ULAMA, 2025)
This study aims to determine the policies of Village-Owned Enterprises and the development of halal tourism that affect the increase in community income. This study uses quantitative methods. The data used in this study are questionnaire data (questionnaires) which are processed into research results. This study uses a total sampling technique and the population in this study were traders at the Aek Milas tourist attraction in Huta Raja village, totaling 33 traders. Among them are garbage stall traders, soto stalls, lontong stalls, warmindo (Indomi food stalls), coffee, and fried food sellers. Analysis of research data using multiple linear regression. The results of the study show that Based on the results of the partial test analysis (t-test) the effect of the BUMDes policy variable (X1) on the variable of increasing community income (Y) with a t count value of -2.480 t table 1.697 and a significance level of the BUMDes policy variable (X1) 0.019 <0.05. The results show that the BUMDes policy variable (X1) partially has a significant and negative effect on the variable of increasing community income (Y) of Aek Milas Dano Hutaraja Hot Springs. Based on the results of the partial test analysis (t-test) the effect of the halal tourism development variable (X2) on the variable of increasing community income (Y) with a calculated t value of 7.369> t table 1.697 and a significance level of the halal tourism development variable (X2) 0.000 <0.05. The results show that the halal tourism development variable (X2) partially has a significant and positive effect on the variable of increasing community income (Y) of Aek Milas Dano Hutaraja Hot Springs.